基于层级疏水/亲水电极同步除盐和有机物的方法、装置 (2023)
本发明提供一种基于层级疏水/亲水电极同步除盐和有机物的方法、装置，装置包括装置本体和设置于装置本体上的电极，电极具有层级疏水和亲水结构，层级疏水和亲水结构的实现方式包括如下方式1和方式2中的至少一种：方式1：电极的电极材料包含多孔复合材料，多孔复合材料包括亲水性多孔碳和存在于亲水性多孔碳表面的疏水层，疏水层包括由疏水导电聚合物形成的疏水导电聚合物层和/或经疏水改性的金属化合物层；方式2：电极材料包括由亲水性多孔碳形成的亲水性多孔碳层和位于亲水性多孔碳层表面的疏水层，疏水层包括由疏水导电聚合物形成的疏水导电聚合物层和/或经疏水改性的金属化合物层。本发明能够同步高效去除废水中的盐成分和有机物。 The invention provides a method for synchronously removing salt and organic matters based on a hierarchical hydrophobic/hydrophilic electrode and a device thereof, the device comprises a device body and an electrode arranged on the device body, and the electrode has a hierarchical hydrophobic and hydrophilic structure. The implementation mode of the hierarchical hydrophobic and hydrophilic structure comprises at least one of the following mode 1 and mode 2: a mode 1: an electrode material of the electrode comprises a porous composite material, and the porous composite material comprises hydrophilic porous carbon and a hydrophobic layer existing on the surface of the hydrophilic porous carbon; the hydrophobic layer c